UPAYA MENINGKATKAN RESILIENSI MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK HOME ROOM PROGRAM PADA MAHASISWA SEMESTER VI PROGRAM STUDI BK FKIP UNISRI - Azam, Ulul (UNIVERSITAS SLAMET RIYADI, 2015)
The objectives of this study are: (1) to find out the implementation of group guidanceservice using home room program technique in improving the students’ resilience of semester VIstudy program BK FKIP UNISRI; (2) to find out the level of resilience on students of semester VIstudy program BK FKIP UNISRI after the implementation of group guidance services using homeroom program technique. This study is an action research. More specifically, this study wasconducted in the field of guidance and counseling. Therefore, it is called guidance andcounseling action research. Group guidance service using home room program technique toimprove the resilience of students was conducted in two cycles. Every cycle, the counselingservice was provided 2 times. In the implementation of group guidance service using home roomprogram technique, each meeting had four stages which were formation stage, intermediatestage, activity stage, and termination stage. The levels of students’ resilience after being givengroup guidance service using home room program technique are: 5 students in the high categoryand 5 students in the medium category with the average score was 123.3 (medium category).Keywords: group guidance services using home room program technique, resilience, students